THE INFLUENCE OF INFRASTRUCTURE AND ECONOMIC GROWTH ON INCOME IN EQUALITY IN INDONESIA - Nuratul Iklima; Sri Wahyuni; Azka Rizkina (RADJA PUBLIKA, 2025)
This study aims to provide empirical evidence regarding the influence of infrastructure and economic growth on income inequality in Indonesia. This type of research is quantitative research. In this study, the author uses secondary data using time series data for 30 years from 1994 to 2023. The data used in this study are annual data from each variable sourced from the official website (BPS Indonesia). Hypothesis testing in this study uses Ordinary Least Squares (OLS) analysis. Based on the results of the OLS Analysis Test, it shows that 1) Infrastructure has a positive and significant effect on income inequality in Indonesia, this is evidenced by the t-count value5,861,811 moregreater than the t-table 1.7033 and has a probability value of 0.0000 which is smaller than 0.05. 2) Economic growth has a positive and significant effect on income inequality in Indonesia, this is proven by the t-count value3.166159 is greater than t-table1.7033and haveThe probability value of 0.0038 is smaller than 0.05.